Juridical Review of Community Forest Utilization Business Permits (IUPHKm) in the Kibuk HKm Group in Agung Lawangan Subdistrict North Dempo District - Mastriati Hini Hermala Dewi; Herma Diana (Fakultas Hukum Dehasen, 2023)
The 1945 Constitution in Article 33 mandates that the earth and water and the wealth contained therein are controlled by the state and used as much as possible for the prosperity of the people at large. Therefore, it is necessary to implement sustainable development that is environmentally friendly.The scope of development to be achieved is so broad, it must be implemented in stages and continuously. Development will certainly bring changes in society. With the changes in development and the increasing population, it should be adapted to the use of existing natural resources for the sake of the continuity of life of the community itself, both now and in the future. ¬Kibuk 94 Social Community Forest (HKM) was formed in In 2017 based on the Decree of the Ministry of Environment and Forestry No. 5756/MENLKH-PSKL/PKPS/PSL 0/10/2017 concerning the Granting of Community Forest Utilization Business Permits to Kibuk Farmer Groups Covering an Area of ​​400 (Four Hundred) Hectares in the Protected Forest Area in Ahung Village Lawangan, North Dempo District, Pagar Alam City, South Sumatra ProvinceThe topographic conditions are relatively sloping and undulating with the general soil type being Andosol. The garden area is at an altitude of around - 1,800 meters above sea level with an average annual rainfall of 2,500 mm-3000 mm. The wet season is 10 months and the dry season is 2 months, with air humidity ranging from 60% - 85% with air temperatures ranging from 150C - 260C. The types of plants in the protected area are in the coffee (Arabica) plantation area, Pokat Plants